"From Start To Success: Analyzing The Impact Of Entrepreneurial Skills And Family Roles In Roadside Food Court Business" - Sharda, Dr. Parul; Sharma, Dr. Sanjay; Mishra, Dr. Reva; Deliwala, Mr. Yash; Gajera, Dr. Alpesh (Migration Letters, 2024)
The study attempts to examine the mediating role of ‘Family Role and Entrepreneurial Skill Sets’ in the relationship between ‘Ease of Start-up and Entrepreneurial Success’ with respect to unorganized roadside food court businesses. For this, 509 responses are collected using four questionnaire scales viz. ease of start-up (11 items), entrepreneurial success (11 items), family role (8 items) and entrepreneurial skills (7 items). Cronbach’s Alpha Coefficient was calculated for all four scales and the values are observed above 0.86 that support the reliability of the scales. Structural equation model, linear regression and Pearson correlation are applied. Also, discriminant validity was also checked using AVE, CR and HTMT ratio, all the values are found in acceptable range. The result reveals that, family role and entrepreneurial skills significantly mediate the relationship where in ‘indirect effect’ value are observed IDE= 0.748, IDE= 0.712 respectively which are obviously greater than direct effect values. Further, significant relationship is observed amongst the EOS and FR, ES & ESK. Findings support the role of ‘FR and ES’ for EOS & ES in unorganized road side food court business. It also reveals that, new venture start-ups and success conceptualizes in highly able entrepreneurial mind-set equipped with required skill sets.